Carbetocin at Cesarean Delivery for Labour Arrest: A Sequential Allocation Trial to Determine the Effective Dose. Issue 2 (June 2016) - Nguyen-Lu, N.; Carvalho, J.C.; Farine, D.; Seaward, G.; Ye, X.Y.; Balki, M.
Abstract : ( Can J Anesth. 2015;62:866–874) Currently, oxytocin is the primary drug used to reduce the incidence of postpartum hemorrhage. However, oxytocin does have limitations, including a half-life of only 4 to 10 minutes, administration by means of an intravenous infusion, and a high rate of dose-dependent adverse effects. In contrast, carbetocin is administered as a single intravenous dose, but the recommended dosages are not well established. The authors of this study sought to determine an effective dose of carbetocin to provide satisfactory uterine tone following an intrapartum cesarean delivery in parturients whose labors were augmented.